Sustainable Competitive Advantage in the Class C Hospital Industry: A Qualitative Study of Strategic Factors in the Tapal Kuda Region of East Java - Siti Asiyah Anggraeni; Fendy Suhariadi; Fiona Niska Dinda Nadia (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: The healthcare industry is rapidly changing due to technological advancement, policy reform, rising patient expectations, and institutional competition. Class C hospitals in regional areas such as the Tapal Kuda region of East Java face challenges in sustaining competitiveness amid limited resources and dynamic healthcare demands. However, studies on sustainable competitive advantage in the Class C Hospital remain limited. Objective: This study aims to analyze the strategic factors influencing sustainable competitive advantage in Class C hospitals in the Tapal Kuda region of East Java. Methods: This study used a qualitative, descriptive-exploratory approach. Data were collected through semi-structured interviews with eight key informants from four Class C hospitals, including hospital directors, heads of medical services, nursing managers, and healthcare administrators. Field observations and institutional document reviews were also conducted. Informants were selected through purposive sampling, and data were analyzed thematically through data reduction, data display, interpretation, and conclusion drawing. Results: The findings identified six strategic dimensions influencing sustainable competitive advantage: digital transformation, technological innovation, organizational resilience, adaptive leadership, human resource competence, and a patient-centered organizational culture. Electronic medical records and telemedicine were identified as important tools for improving service efficiency, while regional socioeconomic disparities, limited specialist availability, and infrastructure gaps constrained hospital competitiveness. Conclusion: Sustainable competitive advantage in Class C hospitals is multidimensional and depends on organizational adaptability, innovation capability, strategic flexibility, and contextual responsiveness. Hospitals that integrate technology, develop competent human resources, and implement patient-centered services are more likely to achieve long-term sustainability and competitiveness.